Development of 'NutriFit Teen' Mobile Application on Adolescent Knowledge of Chronic Energy Deficiency (CED) Risk - Septian Mugi Rahayu; Eva Priskila; Adisurya Saputra (Sarana Ilmu Indonesia (salnesia), 2026)
Chronic Energy Deficiency (CED) in adolescent girls has long-term effects on growth, reproductive health, and future productivity. Low knowledge of CED among adolescents is one of the main causes of this condition. The use of digital technology, particularly mobile applications, offers great potential for effectively improving adolescent nutrition literacy. This study aimed to develop and evaluate the effectiveness of the educational application